Peningkatan Kreativitas dan Hasil Belajar Matematika melalui Model Creative Problem Solving (CPS) - Sulistyawati, Wening Tri (Jurnal Pendidikan Madrasah, 2025)
This study aims to analyze the implementation of the creative problem solving (CPS) learning model in enhancing students' creativity and learning outcomes in Mathematics. The research subjects are seventh-grade students at MTs Negeri 1 Yogyakarta. This study uses the classroom action research method, which consists of two cycles. Each cycle includes planning, action, observation, and reflection activities. Data analysis uses comparative descriptive by comparing data from each cycle. The results show that the creative problem-solving learning can improve students' creativity and learning outcomes. The percentage of students' creativity completeness increased from 65% in cycle I to 85% in cycle II. Meanwhile, the percentage of students' learning outcomes completeness increased from 67% to 91% in cycle II. The creative problem-solving learning can be applied to students at the madrasah tsanawiyah level.